IMPLEMENTASI PEMBELAJARAN TEMATIK BERBASIS DARING DI MIN 2 OKU MIN 2 OKU SUMATRA SELATAN - Yani Pratiwi; Hoirul Anam; Arinil Haq (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2023)
This research aims to describe the implementation of online-based thematic learning at Madrasah Ibtidaiyah Negeri 2 OKU Selatan. As a media to support online learning, using several online platforms such as Google Classroom as a medium for interaction in web-based virtual classes, and WhatsApp groups to support more concise interactions in online classes based on chat platforms. Researchers used descriptive qualitative research methods so that the use of the two digital platforms could be studied in more depth, starting from the weaknesses to the strengths of each. The research results show that online learning has been implemented well, and utilizes various learning media so that thematic learning is more varied and makes students less bored and understands the material presented more quickly. The obstacles faced are that some students do not have cellphones, the signal cannot be accessed and there is a lack of coordination between students and teachers. Keywords: Tematik, Learning, Online, Min 2 Oku